2007
DOI: 10.11646/zootaxa.1401.3
|View full text |Cite
|
Sign up to set email alerts
|

Descriptions of the tadpoles of two species of Gephyromantis, with a discussion of the phylogenetic origin of direct development in mantellid frogs

Abstract: We describe the larval stages of two Malagasy frog species of the genus Gephyromantis, based on specimens identified by DNA barcoding. The tadpoles of Gephyromantis ambohitra are generalized stream-living Orton type IV type larvae with two lateral small constrictions of the body wall at the plane of spiracle. Gephyromantis pseudoasper tadpoles are characterized by totally keratinised jaw sheaths with hypertrophied indentation, a reduced number of labial tooth rows, enlarged papillae on the oral disc, and a yel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Mantidactylus femoralis), and a very narrow A 2gap (6 to 8% of A 2 ). Tadpoles agreeing with this morphology have been described for G. ambohitra (Randrianiaina et al 2007), and also for G. asper, G. sp. aff.…”
Section: Blommerssupporting
confidence: 72%
See 4 more Smart Citations
“…Mantidactylus femoralis), and a very narrow A 2gap (6 to 8% of A 2 ). Tadpoles agreeing with this morphology have been described for G. ambohitra (Randrianiaina et al 2007), and also for G. asper, G. sp. aff.…”
Section: Blommerssupporting
confidence: 72%
“…However, all these early observations were preliminary and not based on reliable identifications of the larvae or embryos examined. This changed with the work of Randrianiaina et al (2007) who reliably reported (based on molecular species identification) exotrophy in tadpoles of G. ambohitra and G. pseudoasper, and provided detailed morphological descriptions of them.…”
Section: Colouration In Preservativementioning
confidence: 99%
See 3 more Smart Citations